Operando 3D Visualization of Migration and Degradation of a Platinum Cathode Catalyst in a Polymer Electrolyte Fuel Cell. (6th July 2017) - Matsui, Hirosuke; Ishiguro, Nozomu; Uruga, Tomoya; Sekizawa, Oki; Higashi, Kotaro; Maejima, Naoyuki; Tada, Mizuki
Abstract: The three‐dimensional (3D) distribution and oxidation state of a Pt cathode catalyst in a practical membrane electrode assembly (MEA) were visualized in a practical polymer electrolyte fuel cell (PEFC) under fuel‐cell operating conditions. Operando 3D computed‐tomography imaging with X‐ray absorption near edge structure (XANES) spectroscopy (CT‐XANES) clearly revealed the heterogeneous migration and degradation of Pt cathode catalyst in an MEA during accelerated degradation test (ADT) of PEFC. The degradative Pt migration proceeded over the entire cathode catalyst layer and spread to MEA depth direction into the Nafion membrane.